Prognostic evidence of LEF1 isoforms in childhood acute lymphoblastic leukemia. (12th April 2021) - Erbilgin, Yucel; Hatirnaz Ng, Ozden; Can, Ismail; Firtina, Sinem; Kucukcankurt, Fulya; Karaman, Serap; Karakas, Zeynep; Celkan, Tulin Tiraje; Zengin, Emine; Aylan Gelen, Sema; Nihal Ozdemir, Gul; Yildirmak, Yildiz; et al.
Abstract: Introduction: The lymphoid enhancer factor 1 (LEF1) is a DNA‐binding transcription factor that functions in the Wnt signaling pathway. Increased LEF1 activity is associated with progression of several types of cancer including leukemia. Here, we investigated LEF1 isoform expression and genomic variations in acute lymphoblastic leukemia (ALL). Methods: LEF1 isoform expression was evaluated by quantitative real‐time PCR in 87 newly diagnosed childhood ALL patients and controls. Moreover, Western blot analysis was performed for detection of LEF1 expression and the hotspot region of LEF1 was screened by deep sequencing. Results: The LEF1 mRNA expression of B cell ALL patients was higher than the controls ( LEF1 ‐total P = .011, LEF1 ‐long P = .026). Moreover, B‐ALL samples showing higher total LEF1 expression had significantly shorter relapse‐free survival ( P = .008) and overall survival ( P = .011). Although full‐length LEF1 expression was similar to the controls in T‐ALL, 50% (n = 15) of the ALL patients had increased full‐length LEF1 protein expression. Imbalance between short‐ and full‐length LEF1 isoforms may lead to cell survival in ALL. Beside the LEF1 activation, LEF1 gene variations were rarely observed in our cohort. Conclusion: The results indicate that the Wnt pathway may have a pathogenic function in a group of ALL patients and high LEF1 ‐total expression might be a marker for shorter relapse‐free survival time in B cell ALL.